PERILAKU BISNIS BUDIDAYA KOLAM IKAN DI KOTA TASIKMALAYA - Hartoyo, Tedi; Putra, Aquinaldo Sistanto; Putri, Pretisila Kartika; Ruslan, Januar Arifin; Salam, Rudhiana (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2024)
The fisheries sector is a potential sector but with stagnant development in Tasikmalaya City. Hence, the importance of identification of driving factors of entrepreneurial behavior in fisheries sectors emerged. This research aims to study the determinants of entrepreneurial behavior and their effect on fisheries business performance in Tasikmalaya City. The research was conducted in Tamansari and Mangkubumi Districts involving 100 fish farm owners. Structural equation model (SEM) analysis was employed for data analysis. Results revealed the positive influence of individual characteristics and environment influence on entrepreneurial behavior. The results also confirmed the positive effect of entrepreneurial behavior on business performance.